Bibliometric Analysis of Game-Based Learning Trends in Science Subjects in Elementary Schools - Putri, Rachmadiah; Amriyah, Chairul; Yanti, Yuli (Lembaga Intelektual Muda (LIM) Maluku, 2025)
Quality education is greatly influenced by the use of technology, especially in learning in the digital era. This study aims to analyze publication trends related to game-based learning in IPAS subjects in primary schools. The method used is qualitative with a bibliometric approach, where data is collected from publications indexed on Google Scholar using Publish or Perish and VOSviewer software. The research object included 100 documents published between 2023 and 2025. Data analysis techniques included keyword mapping, number of publications, and citation analysis. The results showed an increase in the frequency of publications on game-based learning, with Tuanku Tambusai University of Heroes as the top institution. The main keywords that emerged included 'learning,' 'game-based,' and 'learning media,' reflecting the focus on the interaction between games and the learning process. In conclusion, game-based learning has the potential to increase student motivation and engagement